How on Earth Did You Hear About Us? A Study of Exemplary Rural School Practices in the Upper Midwest - Joseph J. D'Amico; Vickie Nelson (Journal of Research in Rural Education, 2000)
Are there characteristics unique to rural schools and communities that contribute to the success oftheir improvement / efforts? A study commissioned by the Rural Advisory Council of the North Central Regional Educational Laboratory sought an answer to this question in three Midwestern rural schools. We found that being rural, small, poor, insecure about their effectiveness in comparison to larger suburban schools, and well-integrated with their communities had an impact on the success ofthese schools' improvement efforts.